Party government and policy responsiveness. Evidence from three parliamentary democracies. (19th November 2018) - Toshkov, Dimiter; Mäder, Lars; Rasmussen, Anne
Abstract: Does party government moderate the responsiveness of public policy to public opinion? Analysing a new dataset, we examine whether the ability of governments to respond to the public on 306 specific policy issues in Denmark, Germany and the UK is affected by the extent of coalition conflict and by the fit of the considered policy changes with the government preferences. We find a systematic but relatively weak positive impact of public support on the likelihood and speed of policy change. Contrary to expectations, a higher number of coalition partners are not associated with fewer policy changes nor with weaker responsiveness to public opinion. We also find no evidence that responsiveness to public opinion is necessarily weaker for policy changes that go against the preferences of the government. Rather, it appears that public and government support for policy change are substitute resources.